Acceso a justicia laboral en Centroamérica - Bolaños, Fernando (2012)
Access to labor justice in Central AmericaThis paper presents a reflection of general character on the most important values and principles that underlie a system of access to the democratic, efficient and fair labor justice. The paper also tries to establish a systematic connection between the concepts of institutionality and access to justice, referring to the interrelationship between both notions and values that feed one another. For work purposes are mentioned and then analyzed four great subthemes: transparency, balance of parties in the labor process, the issue of speedy justice and the principle of effective judicial guardianship. All the above with references to Central America and Dominican Republic legislation and the jurisprudence of the Inter-American Court of Human Rights.